Analysis Of Interpersonal Conflict, Work Overload, And Work Life Balance On Employees' Job Stress - Muktiyani, Friska; Qristin Violinda,; M Fadjar Darmaputra, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to analyze the effect of Interpersonal Conflict, Work Overload, and Work Life Balance on Employee Work Stress at PT. Pegadaian (Persero) Semarang City Branch. This study uses a quantitative approach with 94 employees as respondents. Data were collected through questionnaires distributed directly and online (Google Form). Sampling was carried out using Non Probability Sampling using saturated samples. Data analysis was carried out using multiple linear regression with SPSS 23. The results showed that Interpersonal Conflict had no effect on Work Stress (significance value = 0.350> 0.05). Work Overload had a positive and significant effect (significance value = 0.000 <0.05). Work Life Balance also had a positive and significant effect on Work Stress (significance value = 0.000 <0.05).